Impedance Analysis and PHIL Demonstration of Reactive Power Oscillations in a Wind Power Plant Using a 4-MW Wind Turbine - Koralewicz, Przemyslaw; Shah, Shahil; Gevorgian, Vahan; Wallen, Robb; Jha, Kapil; Mashtare, Dale; Gadiraju, Kasi Viswanadha Raju; Tiwari, Arvind (Frontiers in Energy Research, 2020)
This paper presents impedance-based analysis, mitigation, and power-hardware-in-the-loop (PHIL) demonstration of reactive power oscillations in a wind power plant using a 4-MW Type III wind turbine. Because such oscillations result from interactions among slower control loops of wind turbines regulating the phasor quantities—such as active power, reactive power, and the magnitude of voltages at the point of interconnection (POI)—we propose a new type of admittance called power-domain admittance for the analysis. The power-domain admittance of a wind turbine gives the transfer function from the frequency and magnitude of the voltages at the POI to the active and reactive power outputs of the turbine. The power-domain admittance responses of the 4-MW wind turbine are measured using a 13.8-kV/7-MVA grid simulator to identify the source of the reactive power oscillations. The power-domain impedance analysis and PHIL experiments are performed to explain how a resonant mode inside the wind turbine manifests as turbine-to-turbine and plant-to-grid reactive power oscillations. It is discovered that higher grid impedance during weak grid conditions improves damping of reactive power oscillations between a wind power plant and the grid; however, a higher grid impedance also increases coupling among wind turbines and the risk of turbine-to-turbine reactive power oscillations. The efficacy of a simple droop-based solution in mitigating reactive power oscillations is demonstrated using power-domain impedance measurements and PHIL experiments. The paper presents power-domain impedance measurement as a powerful tool for the analysis and mitigation of reactive power oscillations in wind power plants.